Hybrid Entrepreneurship and Entrepreneurs’ Well-Being: The Moderating Effect of Role Demands Outside Entrepreneurship - Kuske, Johanna; Schulz, Matthias; Schwens, Christian (Entrepreneurship Theory and Practice, 2025)
Current theorizing on learning during hybrid entrepreneurship is limited in explaining the circumstances under which entrepreneurs’ well-being benefits from a preceding phase in hybrid entrepreneurship. Using existing theory on entrepreneurial learning and role conflict, we argue that interfering demands from roles outside entrepreneurship constrain hybrid entrepreneurs’ ability to transform experiences into skills that protect their well-being when they enter full entrepreneurship. Moreover, we argue that interfering role demands affect female and male hybrid entrepreneurs differently. We test the hypotheses using panel data. Our study contributes to entrepreneurship research on hybrid entrepreneurship, well-being, role conflict, and gender differences.